Wireless power system for left ventricular assist device: Influence of coil design and tissue behavior on efficiency - Almorshidi Hawraa A.; Mahdi Ali Jafer; Nawir Manal Hussain (Journal of Electrical Bioimpedance)
This paper proposes a compact wireless power transfer (WPT) system designed to energize an implanted heart pump. The design integrates several power converters: a buck-boost converter supplied by a 14-volt battery, an H-bridge inverter, a low-pass filter, and a resonant inductive coupling WPT unit. A resistive load of 40 ohms is used to simulate the equivalent pump's operation. To improve efficiency and limit power losses caused by high-frequency skin effects, a Litz wire is utilized. Consequently, a multi-layer transmission coil structure is employed to strengthen coupling and ensure deeper field penetration. The system operates in an open-loop configuration with manual adjustment of the DC-DC converter's duty cycle. A frequency of 6.78 MHz is selected based on the Industrial, Scientific, and Medical band due to its recognized safety and its ability to achieve deeper penetration into biological tissues. To optimize the design, precise mathematical modeling of both the WPT system and the tissue layers is conducted, simulating their impact on electromagnetic field behavior. Simulation results demonstrate an impressive power transfer efficiency of 91% across a separation of 60 mm. It is worth noting that most existing studies focus on low-power wireless energy delivery for internal medical devices; this research advances the field by targeting higher power demands, positioning it as a practical solution for critical applications like heart assist pumps.